Developing from the Village: A Regional Economic Perspective in Indonesia - Hutasuhut, Khairul Ali; Siahaan, Lasma Melinda (Universitas Negeri Padang, 2025)
Village development in Indonesia is one of the main focuses in an effort to strengthen the national economy and achieve equitable development. The research method uses descriptive qualitative with data collection of interviews and documentation. The results showed that the development of adequate infrastructure, access to education and health services, as well as local economic empowerment through tourism and agriculture sectors are crucial factors in advancing villages in Indonesia. Fiscal decentralization policies and village fund programs implemented by the central government have had a positive impact on village development, although challenges remain in terms of implementation and sustainability at the local level. The study also found that active community participation and cooperation between the government, local communities, and the private sector are critical to achieving successful village development. Recommendations include improving the management capacity of village governments, strengthening collaboration between various stakeholders, and developing local innovations that are relevant to the village context. This research provides important insights for policymakers and practitioners in designing more effective interventions for village development in Indonesia.